ISLAM SEBAGAI IDENTITAS SOSIAL DALAM KEMAJEMUKAN DI INDONESIA PERSPEKTIF AHMAD SYAFII MA’ARIF - Rahman, Muhammad Iqbal (UIN Sunan Kalijaga Yogyakarta, 2020)
This study aims to reveal the concepts of multi-identity in Ahmad Syafii Ma'arif's thoughts which are the foundation of the concept of tolerance and relations between religion and the state. This becomes the more point that will be elaborated in this research to give a differentiation of Syafii Maarif's thoughts with the thoughts of other figures who also make the Qur'an as a foundation, but it does not demand that the state visually carry the concept of an Islamic state. This research uses a literature study and data analysis methods using the hermeneutic approach. This study concludes that Ahmad Syafii Ma'arif consistently applies the moral foundations of Islam in the state by not making Islam as a state visual identity but as a social identity. So that Islamic identity is not needed to be raised. With this concept, religion becomes a source of identity that is united in state identity, namely Pancasila. With this concept, the opposition that often occurs in determining the country's identity can be minimized by emphasizing the multi-identity possessed by the people in Indonesia. This concept can also bridge the conflicts that often arise between Islamists and Nationalists regarding this matter.